2011
DOI: 10.1007/s10745-010-9369-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra-cultural Differences in the Importance of Plant Resources and Their Impact on Management Intensification in the Tehuacán Valley, Mexico

Abstract: Management of plant resources is a complex process that involves the interaction of numerous cultural, environmental, economic, and ecological factors Therefore, understanding factors influencing management decisions requires multidisciplinary approaches, including both quantitative and qualitative perspectives. This study explores quantitative approaches as methodological tools with which to identify patterns underlying more intensive management of plant resources. The research was conducted in the village of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Thus, with their high interests and involvement in cultural activities, numerous environmental, cultural, economic and ecological factors can interact with innovative approaches [85]. In addition to these arguments, many experts advised that offering culturally-based management practices to provide solutions in ecosystems can contribute to sustainable service development.…”
Section: Cultural Resource Managementmentioning
confidence: 99%
“…Thus, with their high interests and involvement in cultural activities, numerous environmental, cultural, economic and ecological factors can interact with innovative approaches [85]. In addition to these arguments, many experts advised that offering culturally-based management practices to provide solutions in ecosystems can contribute to sustainable service development.…”
Section: Cultural Resource Managementmentioning
confidence: 99%
“…The management practices were described and categorized based on a management intensity index modified from Blancas et al (2013) and González-Insuasti et al (2011). Indicators used to compute the management index are presented in Table 2.…”
Section: Current Management Practicesmentioning
confidence: 99%
“…However, despite extensive ethnoecological knowledge and awareness of sustainable harvesting practices, market forces might bring communities to abusive harvesting of wild plant resources to meet both market demand and their immediate economic needs (Ghimire et al 2004;Sundriyal and Sundriyal 2004). González-Insuasti et al (2011) suggested a quantitative approach to investigate the determinants of management intensity tested for 20 edible plants under different management forms within a rural community of the Tehuacan Valley, Mexico. Management forms were influenced by socio-cultural variables such as age, education, and occupation as well as food preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better understand the processes of management and domestication it is necessary to incorporate socio-cultural aspects related to the use and valuation of a species (Casas et al, 1996;Blancas et al, 2013), which are distributed inter-culturally and intraculturally (González-Insuasti et al, 2011). Certainly, the values attributed to species by people will affect their incentives to manage them (Guijt, 1998) and to continue using them (Ogle, 2001).…”
Section: Introductionmentioning
confidence: 99%